THE PRODUCTIVITY OF LONGLINE FISHING GEAR IN KM. KAKAP MINA UTAMA - William Disraeli Sinaga; T. Ersti Yulika Sari; Arthur Brown (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Productivity longline is one of the indicators in determining the potential fishing areas. The data used in this study is the catch, the area of the fishing grounds, the number of hook is used, and the temperature and salinity of the waters, the data’s is taken every fishing operation. This study aims to determine the productivity of longline, determine the relationship of productivity with the temperature and salinity of water and describe the species composition of the fish and the frequency of appearance. The method used is the case study method to follow the process of catching up with longline for 12 operations on 15 to April 28, 2015 in the waters of West Sumatra through the Port Ocean Bungus.                  The highest productivity of longline fishing gear is obtained 13,35kg / operation / GT and the lowest productivity was 5,01kg / operation / GT. Species composition catch during fishing operations that have the biggest part is yellow fin tuna with 36.2 %. A high frequency of appearance of the fish is layur fish Layur (Trichiurus Lepturus) 933, 30 % indicate that layur fish caught in each fishing operation. Oceanographic parameters of temperature and salinity has an influence on the productivity of longline fishing gear but the impact is low.       Keyword: Productivity, Longline, Tuna